State of the art on organizational longevity: a systematic literature review - Arias Pineda, Andrés Alberto (Cuadernos de Administración, 2022)
Low business longevity is a worldwide phenomenon afflicting multiple organizations that operate in disparate economic conditions, across various industrial processes, different in size and disparate cultural environments. The opening and internationalization of the economy, as well as the problems associated with the environmental crisis, exacerbate this situation. The ability to adapt and strategic renewal of organizations thus become a fundamental capability to survive in times of globalization and competitiveness. The paper’s objective is to present the state of the art of organizational longevity based on a Systematic Literature Review in two databases (WOS and Scopus) with the help of two software specialized in bibliometric analysis and scientific mapping (Bibliometrix and VOSviewer). Organizational longevity is a growing and consolidating field since it addresses a core problem within management, economics, and the social sciences in general: survival. A trend starts to emerge, which hints at connections between the longevity of organizations and the corporate social responsibility (CSR) practices that they engage in.